Integrating Pedagogical Principles into Digital Language Learning: A Conceptual Review of E-Books and Educational Applications in EFL Contexts - Muhammad Alief Raihan Ramadhan; Perdana Kusuma; Randi Surya Pratama; Rizki Alfajri Firdaus; Hesty Widiastuty (Lembaga Pengembangan Kinerja Dosen, 2025)
The rapid advancement of digital technology has transformed English as a Foreign Language (EFL) education, particularly through the integration of e-books and educational applications. Despite numerous studies examining these tools individually, limited attention has been given to how they can be pedagogically aligned to support sustainable language learning. This study aims to fill that gap by conducting a conceptual review that synthesizes relevant studies, books, and official reports published between 2020 and 2025. The review employed a structured inclusion process emphasizing relevance, credibility, and full-text accessibility from major academic databases such as Scopus, ERIC, and Google Scholar. The thematic analysis revealed four major themes: digital learning concepts, the pedagogical affordances of e-books and educational applications, teachers’ digital competence, and the importance of pedagogical coherence. The findings show that when grounded in constructivist and cognitive learning frameworks, digital tools can enhance learners’ engagement, motivation, and language proficiency. This review highlights the necessity of aligning technological use with sound pedagogical design to achieve meaningful learning outcomes. The study provides practical implications by proposing a pedagogical framework that assists teachers, curriculum designers, and policymakers in effectively integrating e-books and educational applications into EFL instruction. Such integration is expected to foster autonomous, interactive, and sustainable language learning in digital environments.